(untitled) (Research, Society and Development, 2022)
For a work environment to be recognized as inclusive, it is necessary to eliminate the barriers that impede the autonomy of the person with a disability. In information and communication technology (TIC) services, widely used by various work activities, there is still a need to identify informational and technological barriers that prevent their full use by people with visual impairments. Following accessibility recommendations for information systems and using assistive technologies available on the market allow for a better interaction of the limitation of the functional part of these people with the work tools available. The Secretariat of Information and Communication Technology (Setic) of the Court of Justice of Pernambuco (TJPE) currently manages 175 TIC services, which involve systems and equipment, offered to internal and external audiences. This article aims to survey the Setic Service Catalog of the TJPE, identifying the life cycle of services, their characteristics, the user public and the impact of evolutionary change, in order to develop a plan for adapting the accessibility of these services. services for effective use by employees with visual impairments, aiming to provide equal opportunities for everyone to develop their work skills, guaranteeing equality of opportunity for people and productivity for the organization. For that, we used the methodology of literature review, where the results obtained showed that there is a need to verify the accessibility in TIC services and better distribution and standardization of assistive technologies for the visually impaired who work at the TJPE.